(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The purpose of this paper is to analyze the manner in which the war itself and its impacts were viewed in the feminist magazine La voz de mujer, by observing the influence of the World War I on the women’s position in Spain. We start from the assumption that the Spain’s neutrality during the entire war influenced the creation of certain distance towards the war, and that the war is not the dominant topic in the magazine, as opposed to the social and economic changes caused indirectly by the World War I in Spain. The first part of this paper describes the social and historical context in which the female magazines appeared during the World War I in Spain. This is followed by the analysis of the three issues of the magazine La voz de la mujer. We interpret the texts by applying the method of the critical discourse analysis.